Iowa Birdline update, February 26, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for February 26, 1990. Highlights of the update include sightings of two Prairie Falcons, 27 Snow Buntings, an immature Golden Eagle, and an early American Pipit. Also of note were observations from Lake Red Rock of numerous Bald Eagles, Snow Geese, Canada Geese, and a dozen species of Ducks. Epson - sheet feed/flatbed